2019
DOI: 10.3390/mi10120822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bridge-Shaped Microchannel Geometry on the Performance of a Micro Laminar Flow Fuel Cell

Abstract: A laminar flow micro fuel cell comprising of bridge-shaped microchannel is investigated to find out the effects of the cross-section shape of the microchannel on the performance. A parametric study is performed by varying the heights and widths of the channel and bridge shape. Nine different microchannel cross-section shapes are evaluated to find effective microchannel cross-sections by combining three bridge shapes with three channel shapes. A three-dimensional fully coupled numerical model is used to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A numerical model containing Navier-Stokes and Butler-Volmer equations was demonstrated by Muhammad Tanveer et al to research the performance of MFEFCs with a bridgeshaped microchannel. 102 The results proved that wide bridge shape on a narrow channel gained the best performance. Ya-Lu Fu et al reported a novel model based on Lattice Boltzmann method to research critical elements and key geometric parameters about O 2 transport and reaction to enhance MFEFCs performance.…”
Section: Fabrication Technologies Of Mfefcsmentioning
confidence: 84%
See 1 more Smart Citation
“…A numerical model containing Navier-Stokes and Butler-Volmer equations was demonstrated by Muhammad Tanveer et al to research the performance of MFEFCs with a bridgeshaped microchannel. 102 The results proved that wide bridge shape on a narrow channel gained the best performance. Ya-Lu Fu et al reported a novel model based on Lattice Boltzmann method to research critical elements and key geometric parameters about O 2 transport and reaction to enhance MFEFCs performance.…”
Section: Fabrication Technologies Of Mfefcsmentioning
confidence: 84%
“…A numerical model containing Navier–Stokes and Butler–Volmer equations was demonstrated by Muhammad Tanveer et al . to research the performance of MFEFCs with a bridge‐shaped microchannel 102 . The results proved that wide bridge shape on a narrow channel gained the best performance.…”
Section: Advances In Recent Yearsmentioning
confidence: 95%
“…This indicates that WI was quite sensitive to the performance of the MMFC with the double-bridge structure. Tanveer and Kim et al [37] studied the influence of the bridge height on the performance of an MMFC with the single-bridge channel. They found that as the bridge height (h) increased to a critical value, the power density increased.…”
Section: Resultsmentioning
confidence: 99%
“…Tanveer and Kim [35,36] investigated the inlets located at the center of microchannels as well as microchannels supporting multiple inlets to mitigate the thickness of the diffusive mixing region and the associated ohmic and mass transfer losses to augment the performance of an MMFC. In addition, Tanveer and Kim [36,37] investigated a bridge-shaped MMFC with multiple inlets, which reduced the mixing layer thickness at the end of each channel. Shaegh et al [23] and Krishnamurthy et al [29] investigated the effects of the electrode structure and arrangement, fuel utilization, and fuel crossover on the performance of an MMFC.…”
Section: Introductionmentioning
confidence: 99%
“…Montesinos et al 41,42 studied an MMFC with a bridge-shaped microchannel experimentally and numerically to enhance the performance of the MMFC. Furthermore, Tanveer and Kim 43 investigated an MMFC for various simple bridge-shaped structures and their impacts on performance of the MMFC.…”
Section: Introductionmentioning
confidence: 99%